2022
DOI: 10.1002/qre.3186
|View full text |Cite
|
Sign up to set email alerts
|

Run sum ratio chart when measurement errors are present

Abstract: As far as literature of quality control is concerned, this is the first article that advocates the run sum ratio scheme with measurement errors, called the RS‐RZ ME chart. The linear covariate error model is employed in designing the RS‐RZ ME chart in detecting increases and decreases in the ratio of two variables from the normal distribution. The average run length and expected average run length values of the RS‐RZ ME chart are obtained using the Markov chain model. A comparison of the RS‐RZ ME scheme with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A linear covariate error model was put forth by 1 when control charts with measurement error were taken into account. In recent years, numerous scholars have employed this paradigm extensively; see 2,3,4,5,6,7,8 . All of these studies showed that measurement error had a negative impact on the performances of control charts, making control charts perform worse.…”
Section: Introductionmentioning
confidence: 99%
“…A linear covariate error model was put forth by 1 when control charts with measurement error were taken into account. In recent years, numerous scholars have employed this paradigm extensively; see 2,3,4,5,6,7,8 . All of these studies showed that measurement error had a negative impact on the performances of control charts, making control charts perform worse.…”
Section: Introductionmentioning
confidence: 99%